2022
DOI: 10.1093/ve/veac063
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ACE2-independent SARS-CoV-2 infection and mouse adaption after passage in cells expressing human and mouse ACE2

Abstract: Human ACE2 (hACE2) is the key cell attachment and entry receptor for SARS-CoV-2, with the original SARS-CoV-2 isolates unable to use mouse ACE2 (mACE2). Herein we describe the emergence of a SARS-CoV-2 strain capable of ACE2-independent infection, and evolution of mouse-adapted SARS-CoV-2 by in vitro serial passaging of virus in co-cultures of cell lines expressing hACE2 and mACE2. Mouse-adapted viruses evolved with up to five amino acid changes in the spike protein, all of which have been seen in human isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 101 publications
(137 reference statements)
2
57
0
Order By: Relevance
“…An alternative to using hACE2 transgenic mice is the generation of mouse-adapted viruses that can utilize mACE2, allowing infection of wild-type mice [ 62 68 ]. To compare the gene expression profile induced by mouse-adapted SARS-CoV-2 to that observed in humans, we analyzed previously published data derived from C57BL/6J mice infected with the mouse-adapted SARS-CoV-2 strain, MA1 [ 68 ] ( Table 1 ). Using an identical analysis pipeline to that used in the current study, Yan et al reported 1027 DEGs due to MA1 infection at 4 dpi, of which 825 were scoDEGs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An alternative to using hACE2 transgenic mice is the generation of mouse-adapted viruses that can utilize mACE2, allowing infection of wild-type mice [ 62 68 ]. To compare the gene expression profile induced by mouse-adapted SARS-CoV-2 to that observed in humans, we analyzed previously published data derived from C57BL/6J mice infected with the mouse-adapted SARS-CoV-2 strain, MA1 [ 68 ] ( Table 1 ). Using an identical analysis pipeline to that used in the current study, Yan et al reported 1027 DEGs due to MA1 infection at 4 dpi, of which 825 were scoDEGs.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative to using hACE2 transgenic mice is the generation of mouse-adapted viruses that can utilize mACE2, allowing infection of wild-type mice [62][63][64][65][66][67][68]. To compare the gene expression profile induced by mouse-adapted SARS-CoV-2 to that observed in humans, we…”
Section: Poor Scodeg Overlap Is Not Dependent On Transgenic Expressio...mentioning
confidence: 99%
See 3 more Smart Citations